A Comparison of Magnetization Transfer Methods to Assess Brain and Cervical Cord Microstructure in Multiple Sclerosis. Issue 2 (5th August 2016) - Lema, Alfonso; Bishop, Courtney; Malik, Omar; Mattoscio, Miriam; Ali, Rehiana; Nicholas, Richard; Muraro, Paolo A.; Matthews, Paul M.; Waldman, Adam D.; Newbould, Rexford D.
ABSTRACT: BACKGROUND: Demyelination is a core pathological feature of multiple sclerosis (MS) and spontaneous remyelination appears to be an important mechanism for repair in the disease. Magnetization transfer ratio imaging (MTR) has been used extensively to evaluate demyelination, although limitations to its specificity are recognized. MT saturation imaging (MTsat) removes some of the T1 dependence of MTR. We have performed a comparative evaluation of MTR and MTsat imaging in a mixed group of subjects with active MS, to explore their relative sensitivity to pathology relevant to explaining clinical outcomes. METHODS: A total of 134 subjects underwent MRI of their brain and cervical spinal cord. Isotropic 3‐dimensional pre‐ and postcontrast T1‐weighted and T2‐weighted fluid‐attenuated inversion recovery (FLAIR) volumes were segmented into brain normal appearing white matter (NAWM), brain WM lesions (WML), normal appearing spinal cord (NASC), and spinal cord lesions. Volumes and metrics for MTR and MTsat histograms were calculated for each region. RESULTS: Significant Spearman correlations were found with the Expanded Disability Status Scale and timed 25‐foot walk for the whole brain and WML MTR, but not in that from the NAWM or any cervical spinal cord region. By contrast, the MTsat was correlated with both disability metrics in all these regions in both the brain and spine. CONCLUSIONS: This study extends prior work relating atrophy and lesion load with disability, by characterization of MTsat parameters. MTsat is practical in routine clinical applications and may be more sensitive to tissue damage than MTR for both brain and cervical spinal cord.